The Application Theory of Planned Behavior to Predict an Indonesian Muslim Student’s Intention to Buy Halal Foods in Taiwan - Ardiyanto, Anang Nur; Lin, Chun-Nan; Maulidah, Silvana; Moh. Shadiqur Rahman; Shaleh, Mohammad Ilyas (HABITAT, 2024)
There are many of foreign students who studying abroad are certainly present an opportunity in it self. Food business become one of the emerging opportunities yet have to address consumer needs. An international student who wants to buy food surely have their own criteria. It is not only about the type and taste of the food but also the other aspect that they need to pay attention the most related to the status of halal food for them who become a Muslim. Halal food are those any kinds of various foods that are  allowed to be eaten and drunk as long as it is suit with the provisions of Islamic law. This study uses Theory of Planned Behaviors to find out the best variables in predicting the purchase intention of halal foods in Taiwan specifically for an Indonesian Muslim students in Taiwan. Online questionnaire using Google Forms was used to predict for amount 342 an Indonesian Muslim students participate as the research sampling. This research used SEM PLS analysis using WarpPLS 7.0 software. For the result, Theory of Planned Behavior  able to be used as a variable to predict the level of purchase intention in halal foods. The Attitude and Subjective Norm has significant result yet the perceived behavioral control has strongly significant results. The last one is about the religiosity that could be used by examine the purchase intention for halal foods as an intervening or mediating variable for this research.